Verocay bodies and myxoid change in fibrosarcomatous variant of dermatofibrosarcoma protuberans: A case report and review of literature - Mary Theresa Sylvia; Bhawana Ashok Badhe (Wolters Kluwer Medknow Publications, 2015)
Dermatofibrosarcoma protuberans (DFSP) is a fibro-histiocytic tumor of intermediate malignant potential. Unusual morphologic patterns can be misleading. Sarcomatous change in DFSP is a rare occurrence. Presence of Verocay bodies and myxoid change in DFSP is uncommon. We report a case where the trucut biopsy was initially reported as neurogenic tumor based on prominent Verocay bodies, myxoid change and increased mitoses. Resection specimen had classic areas of DFSP with foci of Verocay bodies, prominent myxoid change, myofibroblastic differentiation, sarcomatous transformation and a satellite nodule. We also briefly discuss the relevant literature.